Investigating the learning styles among UiTM Melaka TESL students in ESL classroom / Noraina Ayu Roslan - Roslan, Noraina Ayu (2011)
The term ‘learning style’ has been used to describe an individual’s natural, habitual and preferred way of absorbing, processing, and retaining new information and skills This study seeks to investigate the learning style used by the UiTM TESL students based on Index Learning Questionnaire. This study is conducted by adapting the research done by Atef Al-Tamimi and Munir Shuib to the Universiti Sains Malaysia (USM) English major’s students. It is conducted to investigate the learning style used by UiTM Melaka TESL students in learning English as a second language. There are four dimensions of learning style proposed by Felder to define the preferences used by the learners. A set of questionnaire was distributed to 54 final semester TESL students at the City Campus of UiTM Melaka. After analysing the data, it was discovered that UiTM City Campus TESL students had several learning styles focussing on the four dimensions of learning styles designed by Felder and Silverman.